2009
DOI: 10.1111/j.1525-1470.2009.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Nevus Sebaceous and the Risk of Basal Cell Carcinoma: An 18‐Year Review

Abstract: Nevus sebaceous (NS) is a common congenital hamartoma of the skin, usually found on the head and neck. It may undergo malignant transformation to basal cell carcinoma (BCC). However the incidence and lifetime risk of malignant transformation is unknown. We performed an 18-year review of all NS excisions at our institution, to report the number of cases of BCC and other neoplasms within excised NS. The aim is to inform physicians who must weigh the risks in recommending excision of a NS in a pediatric patient p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 18 publications
3
88
1
7
Order By: Relevance
“…cases due to the risk of malignant transformation, but newer studies have shown that the rate of malignancy was grossly overestimated and have drawn confl icting conclusions. Some authors have concluded that observation only is acceptable and excisional biopsy is not necessary, while others still propose prophylactic excision, with disagreements on the timing of treatment (5,(13)(14)(15). If treatment is desired, defi nitive removal of the lesion requires full-thickness surgical excision (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cases due to the risk of malignant transformation, but newer studies have shown that the rate of malignancy was grossly overestimated and have drawn confl icting conclusions. Some authors have concluded that observation only is acceptable and excisional biopsy is not necessary, while others still propose prophylactic excision, with disagreements on the timing of treatment (5,(13)(14)(15). If treatment is desired, defi nitive removal of the lesion requires full-thickness surgical excision (14).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have concluded that observation only is acceptable and excisional biopsy is not necessary, while others still propose prophylactic excision, with disagreements on the timing of treatment (5,(13)(14)(15). If treatment is desired, defi nitive removal of the lesion requires full-thickness surgical excision (14). Th is may be preferred by some patients or parents for cosmetic outcomes or may be indicated due to clinical signs of malignancy such as rapid growth, ulceration, or bleeding (12).…”
Section: Discussionmentioning
confidence: 99%
“…NS are often found on the scalp and, unsurprisingly, tumors arising from within NS occur more frequently on the scalp. 6 The most common tumor types that are found to arise within NS are benign; more specifically, between 90% and 97.5% of tumors developing within NS are benign. 2,3 Trichoblastoma and syringocystadenoma are the most common neoplasms that occur in NS.…”
Section: Bmentioning
confidence: 99%
“…16,17 Nevüs sebaseus da nadir de olsa predispozisyon yaratan diğer bir nedendir. 18 Meksika'da yapılan bir araştırmanın sonucuna göre BCC pediatrik yaş grubunda tüm tü-mörlerin %0,24'ünü ve deri tümörlerinin %13'ünü oluşturmaktadır.…”
Section: Bazal Hücreli̇ Karsi̇nomunclassified